Resilience of cold-water scleractinian corals to ocean acidification: Boron isotopic systematics of pH and saturation state up-regulation - McCulloch, Malcolm; Trotter, Julie; Montagna, Paolo; Falter, Jim; Dunbar, Robert; Freiwald, Andre; Foersterra, Nter; Correa, Matthias Lopez; Maier, Cornelia; Ruggeberg, Andres; Taviani, Marco (Geochimica et Cosmochimica Acta, 2012)
The boron isotope systematics has been determined for azooxanthellate scleractinian corals from a wide range of both deep-sea and shallow-water environments. The aragonitic coral species, Caryophyllia smithii, Desmophyllum dianthus, Enallopsammia rostrata, Lophelia pertusa, and Madrepora oculata, are all found to have relatively high delta B-11 compositions ranging from 23.2 parts per thousand to 28.7 parts per thousand. These values lie substantially above the pH-dependent inorganic seawater borate equilibrium curve, indicative of strong up-regulation of pH of the internal calcifying fluid (pH(cf)), being elevated by similar to 0.6-0.8 units (Delta pH) relative to ambient seawater. In contrast, the deep-sea calcitic coral Corallium sp. has a significantly lower delta B-11 composition of 15.5 parts per thousand, with a corresponding lower Delta pH value of similar to 0.3 units, reflecting the importance of mineralogical control on biological pH up-regulation. The solitary coral D. dianthus was sampled over a wide range of seawater pH(T) and shows an approximate linear correlation with Delta pH(Desmo) = 6.43 - 0.71pH(T) (r(2) = 0.79). An improved correlation is however found with the closely related parameter of seawater aragonite saturation state, where DpHDesmo = 1.09 - 0.14 Omega(arag) (r(2) = 0.95), indicating the important control that carbonate saturation state has on calcification. The ability to up-regulate internal pHcf, and consequently Omega(cf), of the calcifying fluid is therefore a process present in both azooxanthellate and zooxanthellate aragonitic corals, and is attributed to the action of Ca2+-ATPase in modulating the proton gradient between seawater and the site of calcification. These findings also show that the boron isotopic compositions (delta B-11(carb)) of aragonitic corals are highly systematic and consistent with direct uptake of the borate species within the biologically controlled extracellular calcifying medium. We also show that the relatively strong up-regulation of pH and consequent elevation of the internal carbonate saturation state (Omega(cf) similar to 8.5 to similar to 13) at the site of calcification by cold-water corals, facilitates calcification at or in some cases below the aragonite saturation horizon, providing a greater ability to adapt to the already low and now decreasing carbonate ion concentrations. Although providing greater resilience to the effects of ocean acidification and enhancing rates of calcification with increasing temperature, the process of internal pH(cf) up-regulation has an associated energetic cost, and therefore growth-rate cost, of similar to 10% per 0.1 pH unit decrease in seawater pH(T). Furthermore, as the aragonite saturation horizon shoals with rapidly increasing pCO(2) and Omega(arag) < 1, increased dissolution of the exposed skeleton will ultimately limit their survival in the deep oceans. (C) 2012 Elsevier Ltd. All rights reserved.